2015
DOI: 10.1371/journal.pone.0124233
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Serum IgG4 Levels in Patients with IgG4-Related Disease and Other Disorders

Abstract: ObjectiveElevated serum IgG4 levels are an important hallmark for diagnosing IgG4-related disease (IgG4-RD), but can also be observed in other diseases. This study aimed to compare two different testing methods for IgG4: ELISA and nephelometric assay. Both assays were used to measure serum IgG4 concentrations, and to assess the prevalence of high serum IgG4 levels in both IgG4-RD and non-IgG4-RD diseases.MethodsA total of 80 serum samples were tested using the nephelometric assay and ELISA method that we estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
0
14
0
7
Order By: Relevance
“…8 Serum IgG4 levels are not specific markers for IgG4-RD, as they also increase in cancerous, allergic, and autoimmune disorders. 6,9,10 The specificity and positive predictive value of the serum IgG4 for IgG4-RD are 60 and 34% respectively. 11…”
Section: Discussionmentioning
confidence: 99%
“…8 Serum IgG4 levels are not specific markers for IgG4-RD, as they also increase in cancerous, allergic, and autoimmune disorders. 6,9,10 The specificity and positive predictive value of the serum IgG4 for IgG4-RD are 60 and 34% respectively. 11…”
Section: Discussionmentioning
confidence: 99%
“…As increased serum concentrations of IgG4 have been observed in several diseases with aberrant immunological condition unrelated to IgG4-RD, such as malignant tumours, autoimmune diseases especially rheumatoid arthritis and allergic diseases,9 10 increased IgG4 concentration is not a specific marker for IgG4-RD. In contrast, recent large cohort studies from the UK, Taiwan and Japan showed that serum IgG4 concentration >135 mg/dL had overall sensitivities of 82.8%, 86% and 88%, respectively, in diagnosing IgG4-RD 10–12.…”
mentioning
confidence: 99%
“…[5–7] However, tissues from deep organs such as pancreas, retroperitoneum, kidney, ocular cavity, and periaorta are difficult to perform biopsy. In addition, IgG4-RD mainly affects middle-aged to elderly men who often have comorbidities, which places them at risk for complications.…”
Section: Discussionmentioning
confidence: 99%